2012
DOI: 10.2169/internalmedicine.51.6586
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Control and Management Changes in Japan: Questionnaire Survey

Abstract: Background Despite the advances of asthma management and the accompanying improved asthma control, many problems related to asthma management still remain. The Niigata Asthma Treatment Study Group has been regularly collecting information via surveys since 1998 using a questionnaire, on problems related to asthma management; various studies on asthma management have been reported using data from the questionnaire. Methods The aim of this study was to investigate the changes in asthma control and management for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Asthma is a heterogeneous chronic inflammatory disorder of the airways that affects over 300 million people worldwide [1][2][3][4], and is associated with airway hyper-responsiveness and variable airflow obstruction [1]. In Japan, approximately 6%-7% of patients with asthma have severe asthma [5,6], which is characterized by frequent exacerbations and poor symptom control, despite the regular intensive use of maintenance therapies such as high-dose inhaled corticosteroids (ICS) or long-acting b 2 -agonists (LABA) and additional controller medications [7]. In severe asthma, these medications are required to either prevent progression to uncontrolled asthma, or where asthma remains uncontrolled despite these clinical interventions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a heterogeneous chronic inflammatory disorder of the airways that affects over 300 million people worldwide [1][2][3][4], and is associated with airway hyper-responsiveness and variable airflow obstruction [1]. In Japan, approximately 6%-7% of patients with asthma have severe asthma [5,6], which is characterized by frequent exacerbations and poor symptom control, despite the regular intensive use of maintenance therapies such as high-dose inhaled corticosteroids (ICS) or long-acting b 2 -agonists (LABA) and additional controller medications [7]. In severe asthma, these medications are required to either prevent progression to uncontrolled asthma, or where asthma remains uncontrolled despite these clinical interventions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Guideline-based management results in significant improvement in health-related quality of life in most patients 1. Although the goal of therapy is to control asthma by reducing impairment and risk, many patients seem to continue to have some asthma symptoms, such as cough, phlegm, or dyspnea, when asked about their symptoms on a questionnaire 2. Some important complications that occur with asthma, such as rhinitis,3 sinusitis,4,5 and gastroesophageal reflux disease (GERD),6 are known to affect asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent studies have also reported decreases in methylxanthine use for ED patients with acute asthma in other developed nations . Furthermore, similar practice changes have been reported in the primary care setting in Japan . Nevertheless, despite the clinical importance, there has been no study that investigates the current methylxanthine use for acute asthma in Japanese EDs.…”
Section: Introductionmentioning
confidence: 90%